Strategi Pengembangan Bisnis CV. MSA di Majalaya, Kabupaten Bandung, Jawa Barat - Muhammad Devrian Adi Putra; Heny K Suwarsinah; Tanti Novianti (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Textiles industry are one of the largest non-oil and gas commodities produced for export markets segment in Indonesia, these industries create more jobs availability in Indonesia. West Java province is home for many textile industries, Majalaya, one of West Java region well-known for its textile industry products. CV MSA factory located in Majalaya is textile company that specifically produces semi-finished woven fabrics. It is necessary for CV MSA company currently to develop new strategies to increase its capabilities related to increasing productivity and expanding its market segments. Business Model Canvas used as a basis to identify the business model. This research conducted for three months from August until October 2018 by using several internal company data, and summarized into nine business elements in business model canvas (BMC), then break it down into SWOT analysis. Data gathering conducted by observation, in-depth interviews, surveys, FGD, and literature studies. The research sample method was purposive sampling. This research used BMC to identify the business condition and finding internal & external factors. SWOT analysis used for every business model canvas element. All elements used to design the business model canvas for the future business model. Based on elements of business in CV MSA, the managerial implications resulted in six alternative strategies. Keywords: business model canvas, swot, textiles, wovenAbstrak: Industri tekstil di Indonesia adalah salah satu penghasil komoditas ekspor non- migas terbesar Indonesia, industri ini mendorong meningkatnya ketersediaan lapangan kerja di Indonesia. Jawa Barat merupakan provinsi yang memiliki banyak industri tekstil, Majalaya salah satu dari wilayah di Jawa Barat yang dikenal sebagai penghasil produk tekstil.CV MSA yang berlokasi di Majalaya merupakan perusahaan yang bergerak di bidang tekstil yang secara spesifik mengolah benang menjadi kain tenun setengah jadi. Perusahaan membutuhkan pengembangan usaha yang terkait dengan peningkatan efektifitas perusahaan dan penambahan segmen pasar.Penelitian ini ditujukan untuk mengidentifikasi model bisnis CV MSA menggunakan BMC. Penelitian ini menggunakan data yang dirangkum dalam sembilan elemen bisnis yang terdapat pada model bisnis kanvas yang selanjutnya di jabarkan pada analisis SWOT, data yang diambil dalam rentang waktu tiga bulan dari bulan Agustus hingga bulan Oktober 2018. Hasil penelitian yang dihasilkan melalui model bisnis kanvas perbaikan menunjukkan perusahaaan mampu mengembangkan segmen pasar serta melakukan diversifikasi dalam implementasi operasional yang mampu menghasilkan laba bagi perusahaan.Penelitian ini menggunakan pendekatan deskriptif. Berdasarkan hasil analisis dengan menggunakan sembilan elemen dalam bisnis model kanvas CV MSA, implikasi manajerial yang dapat dilakukan oleh manajemen terdiri dari enam macam alternatif strategi. Kata kunci: bisnis model kanvas, swot, tekstil, tenun